COMPARATIVE ASSESSMENT OF QUALITY OF LIFE PARAMETERS IN RURAL AND URBAN RESIDENTS WITH COMORBID HYPERTENSION - Cherkun, M.P.; Katerenchuk, I.P. (World of Medicine and Biology, 2023)
The study highlights the results of a comparative analysis of the quality of life of 152 patients with hypertension and its combined course with type 2 diabetes and coronary heart disease living in urban and rural areas. Quality of life parameters were determined using the SF-36 questionnaire. It was found that the patient's quality of life worsens with increased comorbidity. A clinically significant difference in the quality of life parameters depending on territorial affiliation was established. Thus, the level of quality of life in patients from rural areas is mainly reduced due to the mental component, manifested by a decrease in an emotional state and a decrease in vital activity, while in urban residents – due to the physical part of health, which led to the impossibility of performing everyday tasks.
Keywords: hypertension; SF-36 questionnaire; comorbidity; mental component of health; physical component of health